No Reason to Feel Sick? Nocebo Responses in the Placebo Arms of Experimental Endotoxemia Studies - Benson, Sven; Elsenbruch, Sigrid (Frontiers in Psychiatry, 2019)
Adverse side effects are reported by a large proportion of patients undergoing medical treatment in clinical practice or clinical trials. Nocebo effects, induced by negative treatment expectancies, can contribute to negative patient-reported outcomes but have rarely been studied in the context of inflammatory or immune-related conditions. Based on perceived treatment allocation, we herein analyzed nocebo responders in the placebo arms of randomized controlled double-blind experimental endotoxemia studies. We hypothesized that nocebo responders would report more bodily sickness symptoms and greater mood impairment. Out of N = 106 participants who had all received placebo injection, N = 20 (18.9%) wrongly believed they had received endotoxin and were thus considered as nocebo responders. Nocebo responders reported significantly more bodily sickness symptoms, suggesting that the perception of bodily symptoms affected perceived treatment allocation. Against our expectations, we did not find differences between nocebo responders and controls in psychological or physiological parameters. However, exploratory correlational analysis within nocebo responders revealed that more pronounced bodily sickness symptoms in response to placebo were associated with greater state anxiety and negative mood, as well as with the psychological traits catastrophizing and neuroticism. Our findings support that negative affectivity and personality-related factors may contribute to the reporting of sickness symptoms. Nonspecific symptoms experienced by patients undergoing pharmacological treatments or in randomized controlled trials can be misinterpreted and/or misattributed as unwanted side effects affecting perceived treatment allocation and presumably treatment satisfaction or its perceived efficacy. More nocebo research in the context of acute and chronic inflammatory conditions is warranted.